Design of Mixed‐Cation Tri‐Layered Pb‐Free Halide Perovskites for Optoelectronic Applications. (6th May 2019) - Liu, Zhun; Zhao, Xingang; Zunger, Alex; Zhang, Lijun
Abstract: To eliminate the toxic Pb 2+ cation in hybrid halide perovskites, M′ 3+ cations of Bi/Sb‐based layered halide perovskites are being increasingly investigated for optoelectronic applications. However, such M′ 3+ trivalent cations constrain the face‐sharing bioctahedral or the bi‐layered perovskites required to meet the charge neutrality condition. This usually gives rise to oversized indirect bandgaps and inferior carrier transport. Recent experiment suggested a mixed‐cation tri‐layered halide perovskite can be obtained by sandwiching a [Cu 2+ X6 ] 4− layer between Sb 3+ perovskite bilayers along the polar [111] planes with cation ordering. A material design of mixed‐cation <111>‐oriented tri‐layered Pb‐free halide perovskite A4 MM′2 X12 is studied by a computational screening of various combinations of M 2+ cations (e.g., Zn 2+, Sn 2+ ) and M′ 3+ cations (e.g., Bi 3+, Sb 3+ ). The thermodynamic stability of the candidate materials is systemically evaluated with respect to potential decomposition pathways and a series of stable compounds is synthesized. These results further indicate the chemical trend of electronic structure and how octahedral tilting coupling with charge ordering affects electronic properties. A protocol for engineering A4 MM′2 X12 perovskites with optimized structures and electronic properties by exploiting octahedral tilting coupling with charge ordering in the polar <111> layered perovskites is established. Abstract : A material design of mixed‐cation <111>‐orientated tri‐layered Pb‐free halide perovskites A4 MM′2 X12 by a computational screening of various combination of M 2+ cations (e.g., Zn 2+, Sn 2+ ) and M′ 3+ cations (e.g., Bi 3+, Sb 3+ ) is presented. A protocol for engineering the stable compounds with optimized structures and electronic properties by exploiting octahedral tilting coupling with charge ordering in the layered perovskites is established.